Preparation of RGD-modified liposomes encapsulated with shikonin and its targeted anti-melanoma effects - Hao Zhang; Ying Zhao; Tingting Chen; Xinliang Mao; Jiping Li; Li Fan; Min Li; Xianchun Wen (Frontiers in Oncology)
Melanoma is the most aggressive skin tumor, and conventional treatment is ineffective. Studies have shown that shikonin, derived from the traditional Chinese medicine Lithospermum erythrorhizon, has various anticancer activities. In this work, RGD- modified liposomes encapsulated with shikonin (RGD-Lip-SHK) were prepared by thin- film dispersion, which could highly recognize the integrin αVβ3 on the surface of melanoma cells. RGD-Lip-SHK appeared as spheroid-like vesicles with a particle size of approximately 120 nm, and its ξ-potential was negative. RGD-Lip-SHK remained stable in serum within 48 h and possessed sustained-release effect. In vitro, compared with non -targeted liposomes (Lip-SHK), RGD-Lip-SHK was more efficiently taken up, had higher cytotoxicity, was better targeted to inhibit cell growth, migration, and invasion, and boost cell apoptosis by regulating the expression of Bcl-2 and Bax proteins in melanoma cells. In vivo, RGD-Lip-SHK had the strongest targeted anti-melanoma effect by αVβ3-mediated endocytosis with a long circulation time and inhibited tumor growth in B16F10 tumor-bearing mice compared to other groups. Furthermore, the histology of major organs and the body weight of mice showed that RGD-Lip-SHK had less toxicity. In summary, these results indicated that RGD-Lip-SHK has great potential for the targeted treatment of melanoma, and is expected to become a novel and highly effective strategy for tumor-targeted therapy.